Subject and Academic Setting of Pre-residency Publications as Potential Predictors of Post-residency Academic Productivity in a Cohort of Ophthalmology Residents - Cruz, Franz Marie; Wang, Jiangxia; Joseph, Shannon S.; Miller, Neil R. (Journal of Academic Ophthalmology, 2018)
Objective This study aimed to determine if there is any association between the subject of pre-residency research publications (PRPs) and the academic settings in which they are produced with post-residency academic productivity among graduates from an academic ophthalmology residency program.Design, Setting, Participants This is a cross-sectional study involving graduates of the Wilmer Eye Institute Residency Training Program from 1990 to 1999. An electronic survey was conducted and each participant was asked to submit his/her curriculum vitae, including a list of peer-reviewed publications. Publications were validated and then classified according to the academic setting in which the research was performed, and whether or not the research was related to ophthalmology.Outcome Measures The primary outcome measure was the post-residency academic productivity score. The secondary outcome measures were the relationships of academic productivity with the settings in which PRPs were performed and the topics of the PRPs.Results Fifty-one individuals were included. Regression analysis showed a positive association between the number of PRPs generated during undergraduate studies and medical school and the academic productivity score (ratio = 1.17, p = 0.006) but not during an advanced degree program, research fellowship, or a year off to perform research. Regardless of the setting in which it was performed, the subject of a PRP was not associated with academic productivity.Conclusion It may be appropriate for ophthalmology residency programs whose mission is to train future academicians to place increased weight on applicants who have published articles related to projects performed during undergraduate years or in medical school and less weight on publications related to research performed during a more structured research period, such as an advanced degree program, regardless of the subject(s) of the publication(s).
Keywords: academic productivity; ophthalmology; residency; publications